The fire line : the story of the Granite Mountain Hotshots and one of the deadliest days in American firefighting - Santos, Fernanda (Flatiron Books, 2016)
"Draws on hundreds of hours of interviews with family members, colleagues, historians and other insiders to trace the stories and heroic sacrifices of the elite Granite Mountain Hotshots who gave their lives fighting the catastrophic 2013 wildfire in Yarnell, Arizona,"--NoveList.